Complete Genome Sequence of Isolate Bari 1, a Mild Strain of Cauliflower Mosaic Virus - Ohshima, Kazusato (Microbiol Resour Announc, 2021)
We present here the complete genome sequence of isolate Bari 1, a mild strain of cauliflower mosaic virus (CaMV). The isolate was collected from Diplotaxis tenuifolia (perennial wall-rocket) in Bari, Italy. The genome was 8,020 nucleotides long and shared ≤85.4% nucleotide identity with other CaMV isolates.